The Relationship Between Serum Endocan Levels With the Presence of Slow Coronary Flow: A Cross-Sectional Study. (July 2017) - Kundi, Harun; Gok, Murat; Kiziltunc, Emrullah; Topcuoglu, Canan; Cetin, Mustafa; Cicekcioglu, Hulya; Ugurlu, Burcu; Ulusoy, Feridun Vasfi
Background: The aim of this study was to investigate the relationship between endocan levels with the presence of slow coronary flow (SCF). Methods: In this cross-sectional study, a total of 88 patients, who admitted to our hospital, were included in this study. Of these, 53 patients with SCF and 35 patients with normal coronary flow were included in the final analysis. Coronary flow rates of all patients were determined by the Timi Frame Count (TFC) method. Results: In correlation analysis, endocan levels revealed a significantly positive correlation with high sensitive C-reactive protein and corrected TFC. In multivariate logistic regression analysis, the endocan levels were found as independently associated with the presence of SCF. Finally, using a cutoff level of 2.3, endocan level predicted the presence of SCF with a sensitivity of 77.2% and specificity of 75.2%. Conclusion: In conclusion, our study showed that higher endocan levels were significantly and independently related to the presence of SCF.